Analisis Faktor Produksi dalam Perspektif Islam (Studi Kasus: UKM Keripik Cinta Mas Hendro) - Rani Febriyanni; M. Shabri Abd Majid (Jurnal EMT KITA, 2023)
One of the industrial sectors that make a high contribution to Indonesia's economic growth is Micro, Small and Medium Enterprises (UMKM). One of the UMKM activities in the trade sector in Air Hitam village, Langkat district is the snack food industry named Kripik Cinta Mas Hendro. As an industry that relies on the availability of raw materials from nature, chips entrepreneurs need to participate in protecting the environment so that the availability of raw materials in nature is maintained, in accordance with production activities in the view of Islamic economics. Based on this, the objectives of the first study are, How to implement the production factors of the love chips industry, second, How to implement the production factors for the Cinta chips industry in Air Hitam village, Gebang district, Langkat district in an Islamic perspective. This study uses a qualitative approach with a descriptive type. The results showed that: first, the production factors of the love chips industry had been implemented well in the application of natural resource factors, labor factors, capital factors and management factors. Second, the implementation of the production factors of the love chips industry an Islamic perspective, is all based on Islam.